Innovative method to estimate state of charge of the hydride hydrogen tank: application of fuel cell electric vehicles. (4th March 2022) - Chabane, Djafar; Serairi, Linda; Iqbal, Mehroze; Djerdir, Abdesslem; Fenineche, Nouredine; Elkedim, Omar
ABSTRACT: Significant attention has been paid to metal hydrides (MH) as an environmentally friendly and safe way to store hydrogen. This technology has considerable potential for the application of embedded hydrogen storage in fuel cell electric vehicles, but its widespread application faces a major problem in terms of estimating the remaining hydrogen amount in the tank. In this work, a new method is proposed for estimating the state of charge (SoC) of the hydrogen hydride tank (HHT) by application of piezoelectric material. The idea is to cover the entire inner wall of the metal-hydride tank with a layer of piezoelectric material. During the process of hydrogen absorption, the pressure inside the tank increases, resulting in an increase in the mechanical stress applied to the piezoelectric layer, thus generating a voltage. This effect can therefore be used as an effective means of estimating the amount of hydrogen absorbed. The COMSOL Multiphysics software was used to implement the model and solve the differential equation of energy, mass, and moment. The simulation results showed that the voltage evolution as a function of hydrogen concentration follows the same behavior as the variation of the Pressure Concentration Isotherm (PCI).